Travel website adoption among internet users in Klang Valley, Malaysia - Ahmad, Siti Nor Bayaah; Juhdi, Nurita (Universiti Tun Abdul Razak, 2008)
Studying buyer behaviour is a mystery. It is interesting to study what makes consumers decide to purchase, what factors influence their decisions and how they turn their intentions into actual behaviour. The instrument of act is one of the elements involved in marketing when studying buyer behavior. This instrument is explained in terms of the act of getting the desired object as well as the act involved in consuming the object. Nowadays, the emergence of technology, especially the use of the Internet has helped to reduce the hassle of physically visiting an outlet to find information as well as to purchase a product. The Internet can, technically, minimize consumers’ costs, not only monetary costs but also the cost of time spent in traveling and visiting the store to compare prices. However, despite the benefits derived from the use of this ever ready technology, there are people who are reluctant to use it. The aim of the present study was to examine factors influencing Internet users’ intention to adopt online services for traveling. The survey involved 92 respondents and results indicated that a consumer’s decision to adopt a travel web site service for travelling information and purchasing purposes are determined by several factors. Incorporating the Theory of Planned Behavior proposed by Ajzen and Fishbein, this study revealed that beliefs, social factors (influence), selfefficacy (ability to search for information on the Internet), and travel website effectiveness have significant relationship with consumer intention to adopt travel e-services.